Sistem Pakar Diagnosa Kerusakan Laptop Menggunakan Metode Naïve Bayes-Certainty Factor Berbasis Website - Novitasari; Ria Arafiah; Mulyono (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2023)
Laptop damage is a condition where the laptop malfunctions caused by damaged components in the laptop. According to the ICT Survey and Its Implications for Socio-Cultural and Economic Aspects of Society in Indonesia, 41.55% of Indonesians are computer/laptop users. Seeing that this number is quite large and not everyone can diagnose damage and handle laptop damage, this research is here to build an expert system for diagnosing laptop damage. This study discusses the development of a laptop-based expert system for diagnosing damage website as an effort to provide laptop damage diagnostic services along with suggestions or solutions that can be repair the damage experienced by the user's laptop. This expert system was developed using the methodNaïve Bayes and Certainty factor. The input given to the system is in the form of symptoms of damage experienced, along with its intensity. Method naïve bayes used to find the highest probability of the diagnosis. The results of this diagnosis are then processed using certainty factor to determine the level of confidence in the results of the diagnosis. This expert system comes in the form website built using framework CodeIgniter and MySQL. Based on the results of system testing using 40 expert data, it shows that the expert system for diagnosing laptop damage uses the method Naïve Bayes-Certainty factor shows the suitability of the results of system diagnostics with expert diagnoses that is equal to 85%.